(untitled) (Academicia Globe: Inderscience Research, 2023)
Pumping devices and stations equipped with centrifugal pumps are widely used in agriculture for irrigating land and draining it, for drinking and industrial water supply, and for transporting oil products. Pressure pipes are one of the main structures of pumping stations and devices. These pressure pipes do the main job of transferring water, oil and other liquids without waste. Therefore, pressure pipelines are a technology that saves the fluids being transferred. Therefore, it can be said that scientific research on pressure pipes is an urgent issue of today. Pressure pipes are provided with various fittings (lock, check valve, etc.), that is, equipment. If these fittings do not work normally, the normal operation mode of pumping stations and equipment will be changed.